Small cell neuroendocrine carcinoma of the endometrium and laparoscopic staging: a clinicopathologic study of a case and a brief review of the literature. Issue 4 (1st July 2008) - Bige, O.; Saatli, B.; Secil, M.; Koyuncuoglu, M.; Saygili, U.
Abstract : Small cell neuroendocrine (NE) carcinoma is one of the most aggressive tumors that arise in the female genital tract. Small cell carcinoma of the endometrium (SCCE) is an extremely rare disease. Because of its rarity, the only clinical reports are limited to case studies, and therefore, clinical behavior and optimal treatment modalities are not well defined. To the best of our knowledge, we present the first case of SCCE staged by laparoscopic approach. A 54-year-old parous woman admitted with intermittent vaginal spotting. On physical examination, she had a 4- × 3-cm mass fungating out of the cervical os. Magnetic resonance imaging showed an endometrial mass of 25 × 30 × 50 mm in dimensions, invading less than 50% of the depth of the myometrium at the uterine fundus. Pathologic examination revealed undifferentiated malign NE tumor of endometrium of small cell type. The patient underwent laparoscopic hysterectomy, bilateral salpingo-oophorectomy, and laparoscopic pelvic and para-aortic lymphadenectomy. The disease was surgically staged as IB. Histologically, tumor cells were monotone, with scanty, ill-defined cytoplasm and hyperchromatic nuclei. Immunohistochemically, tumor showed positive immunoreactivity for P16, neuron-specific enolase, and synaptophysin. She underwent pelvic external radiation and brachytherapy postoperatively. Patient has no evidence of disease after 26 months of follow-up. Small cell NE carcinoma of the endometrium is an extremely rare and aggressive disease. With the availability of skilled endoscopic surgeons, laparoscopic management of women, even with SCCE in early stage, can be a feasible option.